Ludruk Arts-Based Historical Learning Innovation as An Improvement of Character Education and Student Learning Resources - Alifi Nur Prasetia Nugroho (History Education, University of Jember, 2023)
To address the complex global challenges of the 21st century, each individual must engage in meaningful learning. This type of research is qualitative with an analytical descriptive approach. This study aims to preserve regional culture that is almost eroded, sothat it is necessary to introduce it to students to revive it.The difference in the way each student learns makes educators rack theirbrains to find and create new learning models so that learning is easily absorbed by students and not boring. Learning material will certainly be interesting if educators are able to convey it creatively. This creativity requires expertise and ideas from educators by utilizing learning media. In the 21st century, history learning is no longer directed at building awareness andnationalism of students alone, but needs to be directed to aspects such as empathy, wisdom, pride in regional culture, the meaning ofnationalism that is not narrow, and patriotism. Ludruk art can improve the character education of students because it takes folklore, history, and everyday life, for example in the remo dance as an opening, ludruk tells about heroism. The results of thisstudy will later contribute to preserving regional culture through education as well as improving the character education of students. Keywords: learning, regional culture, character education, ludruk